2022
DOI: 10.3390/biology11010123
|View full text |Cite
|
Sign up to set email alerts
|

Iron Inhibits the Translation and Activity of the Renal Epithelial Sodium Channel

Abstract: Hypertension is associated with an increased renal expression and activity of the epithelial sodium channel (ENaC) and iron deficiency. Distal tubules absorb iron, causing perturbations that may influence local responses. In this observational study, we investigated the relationship between iron content and ENaC expression and activity using two cell lines and hepcidin knockout mice (a murine model of iron overload). We found that iron did not transcriptionally regulate ENaC in hepcidin knockout mice or in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…As expected, single channel characteristics of various ion channels could be different among species. For example, in Xenopus 2f3 cells the activity of the epithelial sodium channel (ENaC) is 5-7pS (15), but in mouse mpkCCD cells it is 17-20pS (14). Our electrophysiology data showed that the three serine residues within the effector domain of MLP1 plays an essential role in regulating EnNaC activity at the membrane of mAoEC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, single channel characteristics of various ion channels could be different among species. For example, in Xenopus 2f3 cells the activity of the epithelial sodium channel (ENaC) is 5-7pS (15), but in mouse mpkCCD cells it is 17-20pS (14). Our electrophysiology data showed that the three serine residues within the effector domain of MLP1 plays an essential role in regulating EnNaC activity at the membrane of mAoEC.…”
Section: Discussionmentioning
confidence: 99%
“…mAoEC were cultured on glass coverslips and transfected with wild-type or mutant MARCKS constructs. The cells were patched for EnNaC activity using the cell attached configuration 48 hours after transfection as previously described by our group (14). After applying different voltages to the cells an I-V curve was plotted and the conductance of the channel was calculated.…”
Section: Single-channel Patch Clamp Studiesmentioning
confidence: 99%
“…2 Recent studies have demonstrated the importance of iron homeostasis in maintaining the normal functions of suborganelles, such as mitochondria, lysosomes, and the endoplasmic reticulum. 3 Evidence has revealed that a great increase in iron levels occurs when the airway is exposed to tobacco smoke. 4 Excessive iron accumulation has been demonstrated to result in oxidative stress, lipid peroxidation, and finally DNA damage.…”
mentioning
confidence: 99%